Dietary Fe-Gly supplementation attenuates enterotoxigenic Escherichia coli (ETEC)-induced inflammation response and intestinal barrier dysfunction in piglets - Qing Gao; Qing Gao; Qing Gao; Yilong Zhang; Yabin Wu; Dianchao Gu; Junzhou Chen; Conghui Yin; Hao Wu; Dan Zhu; Daiwen Chen; Aimin Wu (Frontiers in Veterinary Science)
Iron in the animal gut that is not utilized by the host can be directly utilized by microorganisms, particularly harmful ones. Organic iron (such as Fe-Gly) has high digestive and absorption efficiency in the body. It is currently unclear whether it can reduce the utilization of iron by ETEC, thereby mitigating the harm caused by ETEC infections. This experiment mainly studies the effects of adding Fe-Gly to the diet on the growth performance, iron nutritional status, and intestinal morphology of weaned piglets infected with ETEC. The study found that adding 50 mg of Fe-Gly to the diet significantly increased ADFI and ADG by 30.6 and 35.3%, respectively (p < 0.05), and alleviated the issues of diarrhea and reduced growth performance caused by ETEC infection. The diarrhea rate decreased by 40% (from 31.25 to 18.75%). In addition to protecting the health of piglets, adding Fe-Gly can also increase the TIBC level in piglet serum (p < 0.05), enhancing their ability to bind and transport iron. From the gene expression results and tissue section results, adding Fe-Gly can also alleviate the damage to the jejunum caused by ETEC challenge to some extent (p < 0.05). In conclusion, adding 50 mg of Fe-Gly can meet the daily needs of piglets, improve iron utilization efficiency, and reduce the residual iron in the intestines. This decreases the iron available for pathogenic microorganisms in the gut, thereby inhibiting the proliferation of intestinal pathogens and ensuring the intestinal health of piglets.